2009
DOI: 10.1007/s00167-009-0941-7
|View full text |Cite
|
Sign up to set email alerts
|

Tendon–bone contact pressure and biomechanical evaluation of a modified suture-bridge technique for rotator cuff repair

Abstract: The aim of the study was to evaluate the time-zero mechanical and footprint properties of a suture-bridge technique for rotator cuff repair in an animal model. Thirty fresh-frozen sheep shoulders were randomly assigned among three investigation groups: (1) cyclic loading, (2) load-to-failure testing, and (3) tendon–bone interface contact pressure measurement. Shoulders were cyclically loaded from 10 to 180 N and displacement to gap formation of 5- and 10-mm at the repair site. Cycles to failure were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Baums MH, in 2010, published a study using the same animal model and pressure film to evaluate different configurations of rotator cuff repair. They highlight the similar characteristics between sheep and human rotator cuff tendons [7].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Baums MH, in 2010, published a study using the same animal model and pressure film to evaluate different configurations of rotator cuff repair. They highlight the similar characteristics between sheep and human rotator cuff tendons [7].…”
Section: Discussionmentioning
confidence: 62%
“…The variables that were evaluated included the maximum contact pressure (mPa), contact surface area (cm 2 ), and percent defect coverage (%) in each of the models. This instrument has been used in various similar studies, which have demonstrated its effectiveness [7,8,17].…”
Section: Measurementsmentioning
confidence: 99%
“…11 Since the suture-bridge repair technique was introduced, several biomechanical studies have shown that the suture-bridge method provides more firm repair constructs than do double-row or single-row repair methods. 2,[32][33][34][35] However, clinical results regarding structural healing following suture-bridge repair have been reported in only 2 studies, to our knowledge. 6,25 Choi et al, 6 who conducted a retrospective case series regarding the suture-bridge technique, reported a 17% retear rate in medium-sized to massive rotator cuff tears.…”
Section: Discussionmentioning
confidence: 95%
“…Animal studies have previously shown that improving tendonto-bone contact pressure increases tendon healing. 22,28 In previous biomechanical studies, double-row repairs have demonstrated consistently better contact pressures compared with single-row repairs, 3,25 and TOE repairs demonstrate greater contact pressure than double-row repairs. 18 Our study found the classic TOE construct to have contact characteristics similar to those reported by prior studies using a similar experimental setup.…”
Section: Discussionmentioning
confidence: 96%